1991
DOI: 10.1007/bf01797616
|View full text |Cite
|
Sign up to set email alerts
|

Erhöhte Prävalenz von Osteoporose und Arteriosklerose bei konventionell substituierter Hypophysenvorderlappeninsuffizienz: Bedarf einer zusätzlichen Wachstumshormonsubstitution?

Abstract: In a retrospective study of 632 patients with pituitary disease we diagnosed pituitary insufficiency without hypersecretion of any pituitary hormone in 122 patients. Patients were substituted with sex hormones (76%), hydrocortisone (74%) and/or L-thyroxine (77%). 76% had additional growth hormone deficiency, as shown by an increase of growth hormone of less than 5 ng/ml after i.v. administration of L-arginine. In 17% of all patients the diagnosis of osteoporosis was proven or suspected radiologically. 57% had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(67 citation statements)
references
References 5 publications
0
67
0
Order By: Relevance
“…A retrospective epidemiological study (6), a cross-sectional radiological study of vertebral heights in GHD patients (7), and data from a pharmacovigiliance study (8) have substantiated the concern by documenting an increased fracture rate in hypopituitary patients. A significant correlation has been found between GH status expressed as peak GH at stimulation test and IGF-I and bone mineral status of lumbar spine and femoral neck (5).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective epidemiological study (6), a cross-sectional radiological study of vertebral heights in GHD patients (7), and data from a pharmacovigiliance study (8) have substantiated the concern by documenting an increased fracture rate in hypopituitary patients. A significant correlation has been found between GH status expressed as peak GH at stimulation test and IGF-I and bone mineral status of lumbar spine and femoral neck (5).…”
Section: Discussionmentioning
confidence: 99%
“…26 Other investigations have also suggested that low circulating IGF-I levels are associated with premature atherogenesis, cardiovascular morbidity, and mortality. 27,28,29 However, these latter studies need to be considered with caution because they were retrospective studies; many subjects in these studies also showed deficiencies of other pituitary hormones, which might have been suboptimally replaced.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced peak bone mass might explain the low bone mineral density among the patients with childhood-onset GHD, but the cause of the osteopenia in the adult-onset GHD is not fully understood. Furthermore, the incidence rate of fractures in hypopituitary patients with adult-onset GHD is not known, although a previous study has indicated an increased risk for osteoporotic vertebral fractures in hypopituitary patients compared with normals (3). We have studied the prevalence of a history of fractures in 107 patients with adult-onset hypopituitarism including GHD with conventional hormonal replacement therapy, except growth hormone (GH).…”
Section: Introductionmentioning
confidence: 99%